2003
DOI: 10.1111/j.1582-4934.2003.tb00231.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of tobacco smoking with GSTM1 gene polymorphism in laringeal cancer

Abstract: This paper aimed to analyze the association of polymorphism of GSTM1 0/0 genotype with laryngeal cancer along a hospital based case‐control study. Polymorphisms of GSTM1 0/0 of samples from 36 patients with laryngeal cancer and 35 healthy controls were detected by PCR method. The reaction used as GSTM1 primers, using the sequence sense: 5′‐CTGCCCTACTTGGATTGATGGG‐3′ and antisense: 5′‐TGGATTGTAGCAGATCATGC‐3′. N Acetyl transferase 1 (NAT1) gene using the primers sense: 5′‐TAAAAGTAAAATGATTTGCTTTCG‐3′ and antisense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Therefore, several authors use laryngeal cancer as an example of how genetic background and environmental exposure interact with a pathological outcome. [26][27][28] The genotype distribution in our Spanish population was found to be in accordance with that previously reported for British and Irish populations. 7,11 The rationale for the analysis performed in this study was based on a previously reported and unexpected association between CAPN10 haplotypes and cancer aggregation.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, several authors use laryngeal cancer as an example of how genetic background and environmental exposure interact with a pathological outcome. [26][27][28] The genotype distribution in our Spanish population was found to be in accordance with that previously reported for British and Irish populations. 7,11 The rationale for the analysis performed in this study was based on a previously reported and unexpected association between CAPN10 haplotypes and cancer aggregation.…”
Section: Discussionsupporting
confidence: 91%
“…Sixteen (28%) (30,35,55,58,62,64,(66)(67)(68)71,72,74,79,(84)(85)(86) of the studies showed a significantly higher risk for HNC in subjects with the null Twenty-three (55%) ORs from 42 studies of the null GSTT1 genotype vs. the positive genotype were >1, and 7 studies (56,64,72,83,85,95,96) showed a significantly higher risk for HNC in subjects with the null genotype than in those with the positive genotype, suggesting that the null GSTT1 genotype may be associated with increased risk for HNC. In contrast, only 1 study showed a significantly lower risk with the null GSTT1 genotype than the positive genotype.…”
Section: Carcinogen Metabolic Genesmentioning
confidence: 99%
“…Sixteen (28%) (30,35,55,58,62,64,(66)(67)(68)71,72,74,79,(84)(85)(86) of the studies showed a significantly higher risk for HNC in subjects with the null GSTM1 genotype than in subjects with the positive genotype. No studies showed a significantly lower risk in patients with the null GSTM1 genotype than in those with the positive genotype.…”
Section: Introductionmentioning
confidence: 98%
“…After a careful review, irrelevant 30 papers were excluded. Then, the remaining 35 papers were examined according to our inclusion criteria and Wnally two concerning CYP1A1 (Lei et al 2002;Varzim et al 2003), ten concerning GSTM1 (Coutelle et al 1997;Jahnke et al 1996;Jourenkova et al 1998;Cabelguenne et al 2001;To-Figueras et al 2002;Bardakci et al 2003;Risch et al 2003;Unal et al 2004;Acar et al 2006;Hong et al 2000) and Wve concerning both of them (Matthias et al 1998;Gronau et al 2003;Li et al 2004;Gajecka et al 2005;Morita et al 1999) were selected. The controls of the included studies are consistent with Hardy-Weinberg equilibrium.…”
Section: Literature Search and Meta-analysis Databasesmentioning
confidence: 99%